Placebo and nocebo effects and their significance in clinical practice - Miro Klarić; Vjekoslav Mandić; Sanjin Lovrić; Martina Krešić Ćorić; Nikolina Zovko (Medicinski glasnik, 2017)
Most people have heard of the placebo effect, while relatively few have heard of nocebo, even within the circles of medical staff. Placebo effect means positive results by treatment via pharmacological inert substances. In contrast to placebo, by nocebo effect, due to negative beliefs and expectations, opposite results are achieved. Said in a more formal manner, what a sick person expects, unfortunately, he/she most often gets. It is a fact that a high number of medical staff is still uninterested in placebo and nocebo effects, although they would benefit from them. Maybe this is because the treatment would not seem “scientific enough”. However, the newest scientific evidence undoubtedly shows that placebo and nocebo effects arise out of very active neurobiological processes intervened by psychological mechanisms such as expectations and conditions. Regardless of whether or not the doctor or the patient are aware of this, placebo and nocebo effects are extremely powerful and represent a significant part of the treatment process, in treatment by methods of ancient cultures, as well as in modern medicine. Of course medicines hold their role, but understanding how the human mind processes information is also very important.
Keywords: awareness; medical staff; mental processes; neurobiology; physicians